How Cooperation Drove the Origin and Evolution of Religion: A Literature Review in the Economics of Religion (Journal for the Study of Religion and History (JSRH), 2025)
The use of economic methods to study and explain the origin and evolution of religion has become an important component of the economics of religion. Compared with disciplines such as religious anthropology, psychology, sociology, and phenomenology, economics often focuses more on the role and effectiveness of the earliest religions in promoting in-group cooperation. That is, religion’s capacity to enhance cooperation within a group is regarded as the principal driving force behind its origin. In explaining the evolution of religion, economics emphasizes the dynamic strategic interaction between religion and other social factors.
Keywords: Economics of religious, cooperation, origin of religion, evolution of religion